Pengaruh suplementasi seng dan vitamin B6 terhadap kadar hemoglobin, hematokrit dan indeks eritrosit pasien malaria vivax yang anemia - Sofiyetti, Sofiyetti; Dharmana, Edi; Rahfiludin, M. Zen; W, Nyoman Suci; Afifah, Diana Nur (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Zinc supplementation decrease the risk of malaria parasitaemia, increasing ferritin serum level and hemoglobin in patients with malaria. Zinc influence the activity of aminolevulinic acid dehydratase (ALAD) an enzymes that catalizes heme synthesize. Vitamin B6 in pyridoxal 5-phosphate (PLP) from has a role in alpha-aminolevulinic acid (ALA) formation, which is the precursor of heme in hemoglobin. PLP also inhibit the growth of the malaria parasite.Objective: The objective was to analyze the effect of zinc and vitamin B6 supplementation on hemoglobin level, hematocrit and erythrocyte indexs (MCV, MCH and MCHC) of anemic Plasmodium vivax malaria patients.Methods: Double Blind Randomised Controlled Trial with pre and post test design. 30 subjects were divided into two groups: the suplementation group were given zinc 1x10 mg/day with vitamin B6 1x5 mg/day and the control group were given a placebo for 30 days. Data analysis by paired t-test, independent t-test and Mann Whitney.Results: There was an increase in Hb levels in the suplementation group (p=0.0001), the control group (p=0.001) and there was a significant difference on the increase between the two groups (p=0.020). Hematocrit significant increase only in the suplementation group (p=0.0001). There were no differences on erythrocyte index parameter in both groups.Conclusion: Zinc and vitamin B6 supplementation of for 30 days increase the hemoglobin level, hematocrit and there were no effect on erythrocyte indexs of anemic Plasmodium vivax malaria patients.